Development of Statistics Teaching Materials: Analysis of The Effect of High Intensity Textual Seductive Detail on The Understanding of Statistics Learning in Psychology Students - Carla Marsha; Desvi Yanti Mukhtar; Sri Supriyantini (Journal of Educational Sciences, 2026)
Statistics courses for psychology students are often considered difficult, requiring teaching materials that enhance engagement without hindering conceptual understanding. One approach is adding textual seductive details—unique but irrelevant narratives or facts—to learning content. This study aimed to develop statistical teaching materials and examine the effect of high-intensity textual seductive details on students’ understanding. Using a one-group pretest–posttest design with 15 psychology students, statistical understanding was measured before and after the intervention and analyzed using the Wilcoxon Signed-Rank Test. Results showed a significant improvement between pretest and posttest scores (Z = −3.041, p = .002, r = .79), indicating a strong positive effect of high-intensity seductive details on learning. Spearman’s correlation revealed no significant relationship between prior knowledge, cognitive load, and posttest results. However, a moderate negative correlation appeared between cognitive load and posttest performance (ρ = −.438; p = .102), suggesting that higher cognitive load tends to reduce understanding, though not significantly. Therefore, integrating high-intensity seductive details should be balanced with careful management of cognitive load in designing statistical learning materials.